Jelajah Sakai: Pengembangan Potensi Ethno-ecotourims Suku Sakai Riau - M. Rawa el Amady (Indonesian Journal of Tourism and Leisure, 2022)
This study discussed the potential for indigenous tourism of Sakai, Riau based on culture and nature. The Sakai tribe in Siak and Bengkalis regencies, Riau, is an indigenous tribe that has a unique culture and nature that is still origin. This paper aims to encourage multi-stakeholders to make the Sakai tribe a tourist destination. This research is a qualitative research, data obtained through observation, and in-depth interviews. The data were analyzed by discussing the theories of indigenous tourism from Hinch & Butler and Smith & Eadington, then written descriptively. This study found that the tourism potential of the Sakai very interesting, namely cultural tourism which includes their daily life starting from marriage, childbirth, economic activities, arts, culture, medical processions, historical tourism and nature tourism. Tourism management requires a collaborative networking effort, thus the Sakai tribe as the main actor in these tourism activities. This paper contributes to the study of indigenous and indigenous tourism, and becomes an important input for the government to develop indigenous tourism.